Hip joint dynamics during the BMX gate start: a case study - Princelle, D.; Domalain, M.; Debril, J. F.; Brunet, E.; Sastre, J.; Monnet, T. (Computer Methods in Biomechanics and Biomedical Engineering, 2020)
The biomechanics of cycling has been examined extensively from different perspectives. It had been shown that a non-seated position increases force production capability of the lower limb and more effectively transfers the force developed by the hip extensors and ankle plantar flexors to the crank, which, in return, reduces mechanical loads on the knee joint (Caldwell et al. 1999). Questions remain about the application of those studies done on a static ergometer in the field. Indeed, in a non-seated posture, cyclists sway their bike laterally underneath their body and this may affect the power generating profile of different joints (Soden et al. 1979). In addition, slope inclination also influences kinematic, kinetics and muscles coordination while pedalling (Duc et al. 2008).